Atheisms: Plural Contexts of Being Godless - Chakraborty, Sanjit (Sophia, 2021)
This special issue of Sophia, titled Living without God: A Multicultural Spectrum of Atheism, deals with the intricate issue of approaching atheism - methodologically as well as conceptually - from the perspective of cultural pluralism. What does "atheism" mean in different cultural contexts? Can this term be applied appropriately to different religious discourses which conceptualize God/gods/Goddess/goddesses (and also godlessness) in hugely divergent ways? Or would that rather be a sort of hegemonic homogenization of all possible modalities of living without God, as Jessica Frazier argues (Frazier 2013, 367)? Is my "God" the same as yours? If not, then how can your atheism be the same as mine? In other words, this issue of Sophia raises the question: Is it not high time that we proposed a comparative study of atheism(s) alongside that of religions, rather than believing that atheism is centered in the "Western" experience? Besides, how can we explore the modalities of atheist religiosity such as we find in Buddhism and Jainism and also, arguably, in certain forms of Hinduism, as far as the Indic traditions are concerned? How might these (re-)negotiations of atheism across the multicultural spectrum interrogate our tendency to place atheism within the context of the binary opposition of science and religion? Besides, there is a need to focus on the philosophical negotiations between atheism, theism and agnosticism and the discourses that emerge from such dialogues, including that of postsecularity.